Changes in design of linings used for trenchless renewal of underground pipelines useing American standards and others related to them - Parka, Anna (Instal, 2022)
The article discusses the most important changes introduced in the American standards and others related to them as regards design of linings used for trenchless renewal of gravity and pressure pipelines. The article also examines the impact of these changes on their thickness. Peculiar attention was paid to the possible and achieved values of their strength parameters as well as their changes over time. General recommendations on the selection of these linings were given too
Keywords: trenchless renewal; linings; gravity and pressure pipelines